2021
DOI: 10.1111/pin.13129
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide analysis of the molecular alterations occurring in the adenomatous and carcinomatous components of the same tumor based on the adenoma–carcinoma sequence

Abstract: Identification of molecular alterations occurring in the adenomatous and carcinomatous components within the same tumor would greatly enhance understanding of the neoplastic progression of colorectal cancer. We examined somatic copy number alterations (SCNAs) and mRNA expression at the corresponding loci involved in the adenoma–carcinoma sequence in the isolated adenomatous and cancer glands of the same tumor in 15 cases of microsatellite‐stable “carcinoma in adenoma,” using genome‐wide SNP and global gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In isolated adenomatous samples, 36 mRNAs showed differential upregulation, and 71 upregulated and 2 downregulated mRNAs were then set from isolated carcinomatous glands within a tumor. The detailed data and a Venn diagram were previously reported ( Figure 4-B ) ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In isolated adenomatous samples, 36 mRNAs showed differential upregulation, and 71 upregulated and 2 downregulated mRNAs were then set from isolated carcinomatous glands within a tumor. The detailed data and a Venn diagram were previously reported ( Figure 4-B ) ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…RT-qPCR was performed using Power SYBR Green PCR Master Mix (Thermo Fisher Scientific) on the CFX96 Touch Real-Time PCR Detection System (Bio-Rad, Hercules, CA, USA). The 2 −Δ Ct method was used to calculate relative gene expression levels based on the Livak and Schmittgen method ( 24 ). The expression levels of each miRNA were compared with that of RNU6B.…”
Section: Methodsmentioning
confidence: 99%
“…It is important for pathologists and gastroenterologists to evaluate the molecular mechanism underlying progression from HGIL to ISL 8 . Although many studies have addressed this mechanism, an effective marker has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that advanced adenomas including HGIL have a high frequency of SCNAs, 8 whereas the number of SCNAs might be higher in metastatic than primary CRC. 20 , 21 Thus, progression from an early‐stage to invasive lesion in CRC seems to involve stepwise accumulation of SCNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation